2012
DOI: 10.1586/ecp.11.68
|View full text |Cite
|
Sign up to set email alerts
|

Pimecrolimus 1% cream for the treatment of seborrheic dermatitis: a systematic review of randomized controlled trials

Abstract: Seborrheic dermatitis is a common, chronic, relapsing inflammatory skin disorder that manifests as erythema, scaling and pruritus in sebum gland-rich areas of the skin. The objective of this article is to evaluate the clinical efficacy of pimecrolimus 1% cream in the treatment of seborrheic dermatitis compared with corticosteroids, antimycotics, placebo or no intervention. Pimecrolimus 1% cream appears to be a well-tolerated and effective treatment for seborrheic dermatitis. It has comparable efficacy, in term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 17 publications
0
13
0
4
Order By: Relevance
“…Furthermore, 0.1% tacrolimus ointment is more effective at reducing symptoms of AD when compared with low-potency corticosteroids, 0.03% tacrolimus and 1% pimecrolimus cream (209). Clinical trials have shown benefit of both pimecrolimus and tacrolimus in seborrhoeic dermatitis, genital lichen sclerosus, intertriginous psoriasis and cutaneous lupus erythematosus and -only for tacrolimus -in resistant pruritus ani (210)(211)(212)(213)(214)(215)(216)(217)(218). Both substances can be used to treat localised forms of CP such as genital pruritus (219).…”
Section: Tacrolimus and Pimecrolimusmentioning
confidence: 99%
“…Furthermore, 0.1% tacrolimus ointment is more effective at reducing symptoms of AD when compared with low-potency corticosteroids, 0.03% tacrolimus and 1% pimecrolimus cream (209). Clinical trials have shown benefit of both pimecrolimus and tacrolimus in seborrhoeic dermatitis, genital lichen sclerosus, intertriginous psoriasis and cutaneous lupus erythematosus and -only for tacrolimus -in resistant pruritus ani (210)(211)(212)(213)(214)(215)(216)(217)(218). Both substances can be used to treat localised forms of CP such as genital pruritus (219).…”
Section: Tacrolimus and Pimecrolimusmentioning
confidence: 99%
“…This mostly pertains to topical steroids that are used in clinical practice to rapidly reduce erythema (Gupta and Versteeg, 2017). When long-term control of the inflammatory response in seborrheic dermatitis is required topical use of the calcineurin inhibitors tacrolimus and pimecrolimus is advised (Ang-Tiu et al, 2012). Safety regarding carcinogenicity of these substances is extrapolated from data in atopic dermatitis and does not seem a reason of concern (Cook and Warshaw, 2009).…”
Section: Treatmentmentioning
confidence: 99%
“…Mittlerweile wurde in RCT der erfolgreiche Einsatz von Pimecrolimus (Elidel ® ) und Tacrolimus (Protopic ® ) bei juckenden, inflammatorischen Dermatosen (z. B. intertriginöse Psoriasis, Pruritus ani, seborrhoisches Ekzem) bei 2 ϫ täglicher Anwendung beschrieben [46][47][48]. In Fallserien und Einzelfallberichten konnte ein antipruritischer Effekt bei Handekzem, genitalem Pruritus, cholestatischem Pruritus bei PBC und nephrogenem Pruritus belegt werden [44,45,49,50,213,214,244].…”
Section: Calcineurininhibitorenunclassified